Penerapan Nilai Toleransi Dalam Kehidupan Mahasiswa : Strategi Untuk Mencegah Diskriminasi Pada Program Studi PAI Universitas Sains Al Quran Wonosobo - Nafi'atus Salmaa Nabila; Dian Mukti Handini; Nurul Mubin (Al Jabiri: Jurnal Ilmiah Studi Islam, 2024)
The phenomenon of intolerance and discrimination is still a significant problem in higher education, including in religion-based institutions. While it is expected to encourage inclusive and open attitudes, various forms of discrimination based on religious, ethnic, or cultural views are still frequent. This study uses a literature review approach to explore the application of tolerance values in preventing discrimination, especially in the context of students of the Islamic Religious Education Study Program (PAI). Through the analysis of theoretical frameworks, previous research, and institutional policies, this research identifies strategies for implementing tolerance in academic and social environments. Findings from the literature show that the value of tolerance is not only able to prevent discrimination but also strengthen harmony and cooperation among students with diverse perspectives. This study recommends the strengthening of tolerance education programs in an ongoing manner and the development of policies to create an inclusive and discrimination-free educational environment, especially in faith-based institutions.